Design of a Web-Based Daily Inpatient Census Information System Interface at the Kanjuruhan Regional General Hospital - Rahmadyo Yudhi Prabowo; Riyan Pramudiya (Jurnal Sehat Indonesia (JUSINDO), 2026)
The Daily Census of Inpatients (Sensus Harian Rawat Inap [SHRI]) at Kanjuruhan Hospital is still carried out manually using spreadsheets, which has the potential to cause reporting delays, data input errors, and low accuracy of information needed for hospital management decision-making. This study aims to design a web-based SHRI information system interface that suits the needs of users and improves the efficiency, accuracy, and quality of recording and reporting of inpatient data. The research uses a descriptive method with a qualitative and quantitative approach. Data were collected through interviews, observations, and questionnaires distributed to inpatient and medical record officers. The evaluation of the interface design was carried out using a usability questionnaire with a Likert scale. The results of the study show that the interface design developed is able to simplify the process of recording and reporting SHRI, improve data accuracy, and speed up information access. The usability evaluation yielded an average score of 84.4%, categorized as satisfied, indicating that the system is well received by users. The web-based SHRI information system interface design is considered effective, easy to use, and in accordance with user needs, thus having the potential to improve the quality of inpatient data management and support hospital management decision-making more optimally.